Perception of indigenous health promoters about health status of their communities, Choco - Colombia - Martínez-Sánchez, Lina María (2023)
Objective: The objective of this study is to explore the perceptions of indigenous health promoters regarding the health status of their communities in Chocó, Colombia. Methodology: This was a cross-sectional descriptive observational study involving Embera indigenous individuals who participated in educational activities related to healthy habits. Eligibility criteria included being over 18 years of age and residing in an Emberá indigenous community for more than one year. Following the educational activities, a survey was conducted, which included questions about the community's health status and lifestyle. The collected information was analyzed, and absolute and relative frequencies were determined. Results: The communities represented by the promoters consisted of more than 51 individuals in 61.9% of cases. Over the course of one year, fewer than 20 pregnant women were reported in 95.2% of the surveyed communities. Regarding access to health services, 71.4% of promoters indicated that the nearest health center was located between 6 and 15 hours away. Concerning lifestyle, 95.2% of the communities boiled water for human consumption, but 70% of them lacked septic tanks. In terms of healthcare, all the communities had a midwife and a herbalist, with 42.9% also having a Jaibaná (indigenous doctor). Conclusion: Health promoters place significant emphasis on proper food and water management, but they express a need for education on waste disposal and recycling. This study has identified a necessity for health training to enable the recognition of prevalent diseases within their communities.